Effort of Domestic Workers to Realize Decent Work: Learning, Organizing and Fighting - Pelupessy, Purnama Sari (Jurnal Perempuan, 2017)
This paper discusses the situation of domestic workers (PRT) and the process of organizing domestic workers that has been doing by the author as a community organizer. The author, with a feminist framework, explores the history of the oppression of women attached to unpaid domestic work and the impact it has on domestic workers who are currently underpaid. This article also discusses the attitude of the state in viewing domestic workers as workers, as citizens and as women as well as the state’s reluctance to ratify the ILO Convention No 189 or ratify the Domestic Workers Protection Bill. The author uses her experience and knowledge in the labor movement and is enriched with the distinctive characteristics of domestic workers. This study concludes that efforts to change the working situation experienced by domestic workers need to be done by organizing domestic workers to have the power to urge thestate to realize decent work.